2023
DOI: 10.25217/ji.v8i1.2699
|View full text |Cite
|
Sign up to set email alerts
|

Development of Interactive E-Modules to Increase Learning Motivation and Science Literacy in Elementary School Students

Christina Ismaniati,
Baroroh Iskhamdhanah

Abstract: The article aimed to  produce interactive e-modules from my country that meets the qualified criteria and to know the effectiveness of the interactive e-modules of my country produced to improve the learning motivation and science literacy of elementary school students of grade IV in the nearby. The research used research and development (R&D), with ADDIE model. The subject of a pilot project for a small group trial consists of 15 students and 1teacher in SD Negeri Soka. Next, the test subject of the field… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 34 publications
0
2
0
Order By: Relevance
“…The findings revealed that teacher empowerment Teaching methods using PDF flip applications, Web, E-Modules LMS teaching materials, Website, Google classroom are relevant to the results of the research (Hafid & Barnoto, 2022) and (Ismaniati & Iskhamdhanah, 2023) that the digital classroom learning management system based on Google workspace for education at SMP Negeri 1 Kedungpring is complete and in accordance with the good curriculum structure established by the government. The findings of this study are backed by research (Astini, 2019) indicating that the following categories of ICT-based learning materials and media can be used by primary school teachers in the learning process: (1).…”
Section: Resultsmentioning
confidence: 80%
“…The findings revealed that teacher empowerment Teaching methods using PDF flip applications, Web, E-Modules LMS teaching materials, Website, Google classroom are relevant to the results of the research (Hafid & Barnoto, 2022) and (Ismaniati & Iskhamdhanah, 2023) that the digital classroom learning management system based on Google workspace for education at SMP Negeri 1 Kedungpring is complete and in accordance with the good curriculum structure established by the government. The findings of this study are backed by research (Astini, 2019) indicating that the following categories of ICT-based learning materials and media can be used by primary school teachers in the learning process: (1).…”
Section: Resultsmentioning
confidence: 80%
“…As stated by Sugiarto et al (2023), andNurjannah et al (2022), stated that the development of physics teaching materials based on analytical skills for students was declared effective as shown from the results of the analytical ability test of students who achieved KBM. In addition Ismaniati et al (2023) and Arifuddin et al (2021), the development and trials that have been carried out on learning tools using electronic modules based on physical science literacy are declared valid, practical and effective so that they are feasible and can be used as alternative physics teaching modules.…”
Section: Results Of the Effectiveness Of Using Science Literacy-based...mentioning
confidence: 99%